Precision cancer medicine: development and future - Markman, Maurie (Henry Stewart Talks, 2020)
What is Precision Cancer Medicine?, What is required for accurate PCM technology?, How to create a PCM system to help the whole population, The use of PCM technology to support patient and family treatment decision making, Combating patient variability in PCM